Matte converting in copper smelting. Issue 1 (3rd April 2019) - Taskinen, Pekka; Akdogan, Guven; Kojo, Ilkka; Lahtinen, Markku; Jokilaakso, Ari
ABSTRACT: Copper matte converting is the key step to ensure high primary copper recovery in the smelting chain. Its development and the fundamental research carried out over the past decades will be reviewed. The operational challenges and environmental concern of batch-wise Peirce-Smith Converting vessel have induced more than 50 years ago attempts to continuous converting process which have materialised in the last two decades in the flash converting technology, utilised currently in one smelter in USA and three smelters in China. Their annual copper production is in excess of 1.5 Mt, and selected fundamental studies behind this major technological invention will be examined.